THE INFLUENCE OF SOCIAL FACTORS ON THE PURCHASE DECISION OF SAMPOERNA CIGARETTES IN MATARAM CITY - Sri Mulyawati (Fakultas Pertanian, Universitas Gunung Rinjani, 2022)
The company offers a variety of products, both in the form of goods and services, to meet the needs and desires of consumers. Cigarettes are a product that almost everyone is familiar with. Even though cigarettes contain several substances that are harmful to the body, for consumers who are already addicted to cigarettes, consuming cigarettes is a basic necessity. This study aims to determine the effect of social factor variables on purchasing decisions for Sampoerna brand cigarettes in the city of Mataram. The type of research used is causal research. This study's population was Mataram City residents who consumed Sampoerna brand cigarettes. The number of samples taken was 50; the sample was determined using a purposive sampling technique, and the data were analyzed using simple linear regression analysis. The results showed that social factors had a positive and insignificant influence on purchasing decisions for Sampoerna brand cigarettes. Based on the result, additional researchers can conduct qualitative research that delves deeper into the impact of social factors on purchasing decisions and other factors that have a significantly impact on cigarette purchasing decisions.